Annual Report 2013: Advancing Climate-Smart Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
As climate changes, can we achieve food security while reducing rural poverty, improving health and nutrition, and sustainably managing our natural resources?